Best of a bad job or masters of illusion: Do nest light conditions make the eggs of brood parasitic brown‐headed cowbirds (Molothrus ater) more similar to the eggs of their hosts?. (20th November 2020) - Rutledge, Samantha; Carr, David E.; Hauber, Mark E.; Hanley, Daniel
Abstract: Brown‐headed cowbirds ( Molothrus ater ) are generalist obligate brood parasites, laying in the nest of nearly 300 avian species, and successfully parasitizing well over 100 host species. Cowbird eggs are generally considered non‐mimetic, although some have suggested that cowbird eggs resemble several of their host species' eggs. To date, no investigation has examined the level of avian‐perceived similarity between cowbird and diverse host eggs in the contexts of light characteristics at the nest and the visual system of the relevant viewer. Because the cowbird exploits a wide range of species that lay in a variety of nest types, hosts view these eggs under an array of light conditions which could facilitate or hinder egg discrimination. When considering the visual system of the relevant viewers and the light conditions at their nest, we found that the coloration of cowbird eggs was more similar to host than non‐host species' eggs. Host responses (whether they accept or reject cowbird eggs) were not statistically different when hosts perceived a large chromatic difference between their own eggs and the cowbird's eggs. Instead, we found that host responses were predicted by the degree to which nesting light conditions facilitated color similarity between host and cowbird eggs, such that hosts typically nesting under light conditions where this color discrimination task was more challenging were more likely to reject cowbird eggs. This suggests that the nesting light environment may have selected for increased coevolved egg recognition abilities in a suite of cowbird host species, even in the absence of parasitic egg color mimicry. Abstract : Hosts of brood parasitic birds can reduce or eliminate the fitness costs of parasitism by recognizing and rejecting foreign eggs from the nest. Here we assessed the avain‐perceived similarity between the colors of host and parasite eggs, to test the role of the nest‐specific lighting environment in modulating the perceived similarity of the eggs of a generalist brood parasite, the brown‐headed cowbird ( Molothrus ater), to those of its hosts. Hosts' eggshell colors were (a) more similar (lower chromatic contrast) to those of the cowbird and (b) species with spotted eggs. In turn, hosts were (c) more likely to reject cowbird eggs when they nest under light conditions where discriminating these eggshell color differences is more challenging.